EXPRESSION OF SUBJECTIVE ATTITUDE IN A SCIENTIFIC TEXT (IN ENGLISH AND UZBEK LANGUAGES) - Shodiev , Ibrohim Majidovich; Sobirova, Intizor Muhammatkulovna (GOLDEN BRAIN, 2024)
This article provides information about scientific text, its types, characteristic features, and artistic text.